Study on the Engagement Characteristics and Control Strategy of High Speed Difference Dry Friction Clutch - Chu Zhu; Zhi Chen; Zongcai Shi; Yingdong Zhang (Machines, 2023)
In the short/vertical take-off and landing aircraft propulsion system, the vertical take-off/landing and rapid flight are switched through the engagement and disconnection of the dry friction clutch. The smooth and rapid connection of the friction clutch is crucial for the mobility and reliability of this type of aircraft. However, the friction clutch vibrates and generates a large amount of heat at high speed, which affects the engagement performance of the clutch. In practice, when the engagement pressure rises quickly, the clutch engagement time is short, and the temperature rise is small, but the impact torque is large, and vice versa. In view of this problem, with a short/vertical take-off aircraft dry friction clutch as the research object, considering the nonlinear variation of friction coefficient and lift fan load torque, the dynamics model and temperature field model of the high speed difference dry friction clutch are established to analyze the clutch engagement time, impact torque, and temperature change. The engagement test at the high speed of the clutch shows that the simulation results of the kinetic model and temperature field model are consistent with the test results. To realize low temperature rise, low impact torque, and short engagement time, the variable slope engagement pressure control method is proposed. Compared with the traditional fixed slope engagement pressure, the proposed variable slope engagement pressure can reduce the engagement time, impact torque and temperature rise simultaneously. The research results can provide a reference for the friction clutch engagement control of short-range take-off and landing aircraft, reduce the development cost of such aircraft, and improve the reliability of the design.